The effect of special exercises using aids in learning the Arabian salto backward stretched off on vault for men artistic gymnastics - Hamza, Jamal Sakran; Addulridah, Nada Ibrahim; Wahid, Ali Abdel (International Journal of Psychosocial Rehabilitation, 2020)
the vault table in the artistic gymnastics mens devices and aids to learn the skill and to identify the impact of these exercises and the researchers used the experimental approach to design the one group with pre and post testing, either the research sample consisted of ( 6) Players from Baghdad, Al-Karkh, at the Youth Challenge Forum, in Emaar (13-16), and they were chosen in an intentional way, and they represent 80% of the parent community. After obtaining the results and statistically treating them, the researchers reached some conclusions and recommendations. The researchers concluded that the auxiliary devices are highly efficient in learning the skill of Arabic with his heart an open background on the jumping device in the technical gymnastics for men. The researchers recommend using a mini trampoline device to learn skills with a higher difficulty The platform to jump and warm up on is in the preparatory part of the daily training unit in order to raise their physical fitness, as well as the use of a mini-trampoline in learning high-difficulty skills on the ground movement rug machine. And in learning some skills on pain Parallel and low-minded as an aid device in the kidnapping for handstand and skill performance.